Study of Coordinated Reactive Power Control for Distribution Grid Voltage Regulation with Photovoltaic Systems - W. Moondee (2019)
© 2019 IEEE. Voltage rise and reverse power flow in the distribution grid with photovoltaic (PV) systems have caused new challenges of the reactive power control method. This paper presents a study of coordinated reactive power control for distribution grid voltage regulation with PV generation. The objectives of this research are to provide the reactive power to support the distribution grid and regulate the PV bus voltage of PV systems. The control method is based on centralized reactive power management in a high voltage (HV) distribution and coordination of voltage-dependent reactive power characteristics for allocating the reactive power to PV systems. The reverse power flow and voltage rise can be controlled by PV systems at the medium voltage (MV) level which contributes to controlling the reactive power exchange between HV and MV voltage levels. The system case consists of a PV system connected to the two radial feeders in the distributed grid. The simulated model of the proposed system is built through DIgSILENT PowerFactory software. Simulation results are presented to validate the effectiveness of the control method for mitigating voltage rise and reverse power flow in the distribution grid with the PV generation.